Total synthesis of verbalactone: an efficient, carbohydrate-based approach - Salunke, Ganesh B.; Shivakumar, I.; Gurjar, Mukund K. (Tetrahedron Letters, 2009)
A carbohydrate-based strategy for the total synthesis of verbalactone has been described. (3R,5R)-3,5-dihydroxydecanoic acid was dimerised under Yamaguchi conditions to provide verbalactone in an overall yield of 17% starting from 3-deoxy-1,2:5,6-di-O-isopropylidine-alpha-D-glucofuranose. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Chiral pool approach; D-Glucose; verbalactone; Yamaguchi's macrolactonization

Cyclopropyl methyl bromide-mediated gem-diallylation: total synthesis of (+/-)-alpha-cuparenone - Shivakumar, I.; Salunke, Ganesh B.; Kumar, Suneel (Synthetic Communications, 2011)
[image omitted] The total synthesis of (+/-)–cuparenone, an aromatic sesquiterpene, has been described using the radical mediated gem-diallylation of substituted cyclopropyl methylbromide followed by ring-closing metathesis approach.
Keywords: Aromatic sesquiterpene; gem-diallylation; Ring-closing metathesis